1997
DOI: 10.1002/jhrc.1240201211
|View full text |Cite
|
Sign up to set email alerts
|

A reversed phase high‐performance liquid chromatography method for determination of cephalexin in human plasma

Abstract: SummaryA reversed-phase HPLC method for the analysis of cephalexin (74 (aminophenylacetyl)amino]-3-methyl-8-oxo-S-thia-l-azabicyclo[4.2.0]oct-2-ene-2-carboxylic acid) by isocratic separation is described. A comparison is made between the ultrafiltration and the extraction procedure developed in our laboratory. The extraction procedure, based on the deproteinization of plasma with perchloric acid followed by the extraction with dichloroethane and separation of cephalexin on a reversed phase column, gave better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Hence the power of study might not be sufficient. Pecavar et al published analytical method to quantify cephalexin in human plasma; however, the method was not applied in any pharmacokinetic study or bioequivalence study 7 . Mohamed et al had conducted a bioequivalence study of three Cephalexin formulations in 24 Sudanese volunteers.…”
Section: Cephalexinmentioning
confidence: 99%
“…Hence the power of study might not be sufficient. Pecavar et al published analytical method to quantify cephalexin in human plasma; however, the method was not applied in any pharmacokinetic study or bioequivalence study 7 . Mohamed et al had conducted a bioequivalence study of three Cephalexin formulations in 24 Sudanese volunteers.…”
Section: Cephalexinmentioning
confidence: 99%
“…[16] Cephalexin is official in IP, [17] United States Pharmacopoeia, [18] and BP. [19] Literature survey revealed that spectrophotometric, [20][21][22] HPLC, [23][24][25][26][27] and one HPLC method [28] have been reported for this combination drug.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing effective analytical methods for the sensitive and selective detection of trace amounts of cephalexin is especially important. Compared with many other methods, like highperformance liquid chromatography (HPLC), 3 liquid chromatography (LC), 4 ow injection analysis, 5 electrochemical methods, 6 uorescence assays have several advantages, such as high sensitivity and fast analysis. However, to the best of our knowledge, the use of uorescence probe for analysis of cephalexin is very rare.…”
Section: Introductionmentioning
confidence: 99%